Knowledge and behavior of mothers about the way of suckling their babies - Titi S. Sularyo; Rini Sekartini; Soedjatmiko Soedjatmiko; Hartono Gunardi; Corrie Wawolumaya (Indonesian Pediatric Society, 2002)
Background A good and proper knowledge and behavior of mothers as to how they breast-feed their young is supposed to enhance the health of the community.Objective To find out the knowledge and behavior of mothers of under-fives about the technique of nursing and its related factors.Methods The study was perionned from September 20 to October 15, 1999 at Kelurahan Pisangan Baru, East Jakarta. The respondents were 101 mothers owning under-fives, attained by the multi-stage cluster random sampling method. Questionnaires were used and observation was made only on mothers who were suckling their child during the interview.Results Mother's knowledge about the way of suckling was found unsatisfactory in 46.5% although 51.5% of mothers revealed a good behavior. Statistical analysis showed no significant relationships between factors such as age, educational level, occupation, family income and mother's activity with mother's knowledge and behaviorabout the way of nursing their child.Conclusions There was no significant relationship between mother's knowledge and behavior about breastfeeding. Other factors beyond this studied factors should be taken into account.